Decentralization Process of Rural Development Policy in Greece - Pavlos Karanikolas; Sofia Hatzipanteli (European Regional Science Association (ERSA), 2006)
The decentralization process of national administrative systems, the continuous evolution of structural policies in the EU and the increasing reinforcement of the second Pillar of the Common Agricultural Policy, create an entirely new setting in the field of rural policy making and implementation. A significant decentralization process of agricultural and rural development policies is taking place in Greece, by means of the establishment of a novel institutional framework and reallocation of administrative competencies. Drawing upon a case study of the farm modernization scheme, a pivotal rural development policy measure, this study aims at critically assessing the decentralization process of rural policy making and delivery in Greece within the new institutional and administrative setting. Research findings indicate that despite remarkable decentralization efforts, rural development in Greece seems to maintain its primarily state-emanated design and implementation, in a centralized logic. Long standing top-down and sectoral orientation in the formulation of this policy still holds, permeating the attitude of a number of actors, whose traditional role is challenged in the new setting. The redistribution of responsibilities and the mere multiplication of competent authorities do not necessarily advance the policy outcomes. What is needed as well is a genuine delegation of competencies and resources, coupled with a renewed awareness of integrated policies from the actors involved at all administrative levels.
Keywords: 330